On the Usefulness of the Pragmatic Perspective in Translation: the case of the Speech Acts in the EU Legal Texts - Mihaela COZMA (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Based on the belief that the choice of any lexical or grammatical item depends not only on the meaning or on the use perceived as conventional in a particular language, but also on a wide range of contextual variables, the present paper argues for the necessity and the usefulness of adopting a pragmatic perspective at various stages of the translation process. For illustration, the author focuses on the specific features presented by the speech acts predominantly used in the English versus the Romanian variants of the EU legal texts, and especially on the illocutionary force with which they are associated.